Hemodynamic effects of HPMA copolymer based doxorubicin conjugate: A randomized controlled and comparative spectral study in conscious rats. Issue 2 (7th February 2017) - Cheah, Hoay Yan; Šarenac, Olivera; Arroyo, Juan J.; Vasić, Marko; Lozić, Maja; Glumac, Sofija; Hoe, See Ziau; Hindmarch, Charles Colin Thomas; Murphy, David; Kiew, Lik Voon; Lee, Hong Boon; Vicent, María J.; et al.
Abstract: Conjugation of Doxorubicin (DOX) to N -(2-hydroxypropyl) methylacrylamide copolymer (HPMA) has significantly reduced the DOX-associated cardiotoxicity. However, the reports on the impact of HPMA–DOX conjugates on the cardiovascular system such as blood pressure (BP) and heart rate (HR) were in restrained animals using tail cuff and/or other methods that lacked the resolution and sensitivity. Herein, we employed radiotelemetric-spectral-echocardiography approach to further understand the in vivo cardiovascular hemodynamics and variability post administration of free DOX and HPMA–DOX. Rats implanted with radio-telemetry device were administered intravenously with DOX (5 mg/kg), HPMA–DOX (5 mg DOX equivalent/kg) and HPMA copolymer and subjected to continuous cardiovascular monitoring and echocardiography for 140 days. We found that DOX-treated rats had ruffled fur, reduced body weight (BW) and a low survival rate. Although BP and HR were normal, spectral analysis indicated that their BP and HR variabilities were reduced. All rats exhibited typical signs of cardiotoxicity at histopathology. In contrast, HPMA–DOX rats gained weight over time and survived. Although BP, HR and related variabilities were unaffected, the left ventricular end diastolic volume (EDV) of these rats, as well as of the HPMA copolymer-treated rats, was found increased at the end of observation period. Additionally, HPMA copolymer caused microscopic injury of the heart tissue. All of these suggest the necessity of caution when employing HPMA as carrier for prolonged drug delivery. The current study also indicates the potential of radiotelemetric-spectral-echocardiography approach for improved preclinical cardiovascular risk assessment of polymer–drug conjugate and other nano-sized-drug constructs.